Prevention of pancreatic cancer - Kuroczycki-Saniutycz, Stefan; Grzeszczuk, Agnieszka; Zwierz, Zbigniew Wojciech; Kołodziejczyk, Paweł; Szczesiul, Jakub; Zalewska-Szajda, Beata; Ościłowicz, Krystyna; Waszkiewicz, Napoleon; Zwierz, Krzysztof; Dariusz Szajda, Sławomir (Contemporary Oncology/Współczesna Onkologia, 2017)
Pancreatic ductal adenocarcinoma (PDA) accounts for 95% of all pancreatic cancers. About 230,000 PDA cases are diagnosed worldwide each year. PDA has the lowest five-year survival rate as compared to others cancers. PDA in Poland is the fifth leading cause of death after lung, stomach, colon and breast cancer. In our paper we have analysed the newest epidemiological research, some of it controversial, to establish the best practical solution for pancreatic cancer prevention in the healthy population as well as treatment for patients already diagnosed with pancreatic cancer. We found that PDA occurs quite frequently but is usually diagnosed too late, at its advanced stage. Screening for PDA is not very well defined except in subgroups of high-risk individuals with genetic disorders or with chronic pancreatitis. We present convincing, probable, and suggestive risk factors associated with pancreatic cancer, many of which are modifiable and should be introduced and implemented in our society.